ASURANSI JIWA ENDOWMENT DENGAN PENGEMBALIAN PREMI MENGGUNAKAN SIMULASI MONTE CARLO - HENDRAWAN, MADE EDI; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 8 No 2 (2019), 2019)
Premium refunds are a sum of the money returned to the insured. The purpose of this study was to compare the premium of endowment life insurance with premium refund on constant interest rates numerical calculations and using Monte Carlo simulations. Gompertz distribution was used to obtain the mortality rates. The results showed that the premiums generated by Monte Carlo simulations for insurance participants issued under 45 years will be more expensive than the ones which were generated by numerical calculations. However, the premiums generated by Monte Carlo simulations for insurance participants issued above 45 years will be cheaper than the ones which were generated by numerical calculations.